How Did Japanese Investments Influence International Art Prices? - Hiraki, Takato; Ito, Akitoshi; Spieth, Darius A.; Takezawa, Naoya (Journal of Financial and Quantitative Analysis, 2009)
Abstract We test the luxury consumption hypothesis of Ait-Sahalia, Parker, and Yogo (2004), using a unique international art price, import/export flow, and stock market data set. We find that the demand for art by Japanese collectors is positively correlated with art prices and Japanese stock prices. This correlation is magnified during the “bubble period” of the Japanese economy (the mid-1980s to the early 1990s) and gains even further strength for works of art typically favored by Japanese collectors. Our results suggest that Japanese investors (or Japanese asset markets) indeed affect international art prices—especially during the bubble period and its aftermath.